2022
DOI: 10.3389/fpls.2022.952732
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of proline-rich proteins and hybrid proline-rich proteins super family genes from Sorghum bicolor and their expression patterns to abiotic stress and zinc stimuli

Abstract: Systematic genome-wide analysis of Sorghum bicolor revealed the identification of a total of 48 homologous genes comprising 21 proline-rich proteins (PRPs) and 27 hybrid proline-rich proteins (HyPRPs). Comprehensive scrutiny of these gene homologs was conducted for gene structure, phylogenetic investigations, chromosome mapping, and subcellular localization of proteins. Promoter analysis uncovered the regions rich with phosphorous- (BIHD), ammonium-, sulfur-responsive (SURE), and iron starvation-responsive (IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 129 publications
1
2
0
3
Order By: Relevance
“…These findings suggest that proline-rich proteins are emitted into the extracellular medium via the signal peptide. Our findings indicate that proline rich-proteins and their homologous gene (HYC85_019506) might be involved in plant immunity and performance, and our results are consistent with the findings of [ 37 , 38 ]. Moving forward, early light-induced protein 1 was only decreased under (dCK_vs_dSD60).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings suggest that proline-rich proteins are emitted into the extracellular medium via the signal peptide. Our findings indicate that proline rich-proteins and their homologous gene (HYC85_019506) might be involved in plant immunity and performance, and our results are consistent with the findings of [ 37 , 38 ]. Moving forward, early light-induced protein 1 was only decreased under (dCK_vs_dSD60).…”
Section: Discussionsupporting
confidence: 91%
“…This protein carries out extracellular repairing and programming in tea leaves. Based on a recent phylogenetic analysis, the authors reported that genes-encoding peptides of proline rich-proteins had been scattered in the chloroplast, extracellular medium, mitochondria, nucleus, and cytoplasm; nevertheless, the chloroplast and extracellular medium are the main points for their localization [ 37 ]. These findings suggest that proline-rich proteins are emitted into the extracellular medium via the signal peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Виняткову роль у підтриманні активності людства відіграють злаки, серед яких значне місце посідає пшениця. Більш того, дослідники вважають, що значення пшениці майбутньому буде зростати і саме ця культура стане провідною [1,2,3,18,34]. Розповсюдження пшениці обумовлено високою поживністю зерна, із якого отримують багато харчових продуктів, а також її високою біологічною пластичністю стосовно екологічних умов.…”
Section: вступunclassified
“…Тому завдання отримання стійких до абіотичних факторів форм рослин стає першочерговим. Для України в першу чергу воно пов'язано із пшеницею озимою [1,3,7,11,18].…”
Section: вступunclassified
See 1 more Smart Citation